1992
DOI: 10.1103/physrevlett.68.919
|View full text |Cite
|
Sign up to set email alerts
|

Location of the low-energy1Ag

Abstract: The two-photon excitation spectrum in polycrystalline a-sexithienyl (7^) thin film has been investigated at 4.2 K in the spectral range between 910 and 1180 nm of the fundamental laser radiation. The intense two-photon absorption band at 18 350 cm -1 is assigned to the 2 l A g exciton band origin. The comparison of the one-photon and two-photon excitation spectra shows that the lowest "gerade" exciton level lies at 898 cm -l above the lowest one-photon-allowed 1 ] B U exciton level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1

Year Published

1995
1995
1999
1999

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(41 citation statements)
references
References 28 publications
(31 reference statements)
2
38
1
Order By: Relevance
“…Earlier work has shown that the lowest optically forbidden excited state 2A g lies below the optically allowed excited state 1B u in polyene molecules [2] ( thus preventing any significant luminescence in such compounds ), while an independent electron model gives the opposite picture; similar results have been found by Periasamy et al in the case of polycrystalline sexithienyl [3] or Lawrence et al in single crystal polydiacetylene [4]. These examples serve as evident manifestation of electron correlation in conjugated molecules.…”
supporting
confidence: 72%
“…Earlier work has shown that the lowest optically forbidden excited state 2A g lies below the optically allowed excited state 1B u in polyene molecules [2] ( thus preventing any significant luminescence in such compounds ), while an independent electron model gives the opposite picture; similar results have been found by Periasamy et al in the case of polycrystalline sexithienyl [3] or Lawrence et al in single crystal polydiacetylene [4]. These examples serve as evident manifestation of electron correlation in conjugated molecules.…”
supporting
confidence: 72%
“…It is experimentally known that for the longer all-trans polyenes, starting with hexatriene, 11 the lowest singlet 0-0 transition corresponds to an electronic state of the same symmetry as the ground state ͑for example, in dodecahexaene the 2 1 B transition in bithiophene. 2 The fact that the energy difference between these two 0-0 bands is much smaller in hexathiophene ͑0.11 eV͒, although the same ordering is found, suggests that the reversed order prevails for longer chains ͑Ͼ6 monomer units͒, that is, 2 1 A is below 1 1 B. Periasamy et al 12,13 have, however, suggested that the electronic energetics of ''real'' polythiophene follows the same excited states ordering as in hexathiophene based on the similarity observed between the photoluminescence of the polymer and the oligomer.…”
Section: Introductionmentioning
confidence: 86%
“…Although the vertical excitation energies place the 2 claim that the two lowest excited states of thiophene oligomers and polyenes are similar, and therefore the lowest excited state is predicted to have the same symmetry as the ground state, which is contrary to the experimental evidence. 1,2,12,13 In order to explain the experimental information, they suggest that the 1 A g experimentally observed is the 3 1 A g state. Here, one could note that a comparison of the two lowest excited states of 1,3 cis-butadiene and thiophene shows important differences.…”
Section: Introductionmentioning
confidence: 99%
“…Among organic molecules, ␣-hexathiophene (T6) is a well-characterized prototypical compound for polyconjugated systems. [5][6][7][8][9][10][11][12] Furthermore, T6 possesses interesting properties of hole injection into highly fluorescent polymers. 13 It is then of utmost importance, in order to engineer new materials with suitable optoelectronic properties, to understand the essential processes in which T6 molecules form solid structures and to what extent their order can be driven by the substrate structure.…”
mentioning
confidence: 99%